The use and regulation of framework agreements in Chinese public procurement - Ren, Ke (2019)
Framework agreements have been widely used in Chinese public procurement for over two decades. However, the regulation is far behind the practice. There are currently neither legal rules nor a uniform definition of framework agreements in Chinese laws and regulations on public procurement at the national level. Legal uncertainty and inappropriate use of framework agreements in practice, which have attracted a significant amount of public criticism, have not been thoroughly analysed by the literature.